Deutsch als Fremdsprache : ein internationales Handbuch. - Helbig, Gerhard (Handbücher zur Sprach- und Kommunikationswissenschaft ;, 2001)
This series of HANDBOOKS OF LINGUISTICS AND COMMUNICATION SCIENCE is designed to illuminate a field which not only includes general linguistics and the study of linguistics as applied to specific languages, but also covers those more recent areas which have developed from the increasing body of research into the manifold forms of communicative action and interaction. For ""classic"" linguistics there appears to be a need for a review of the state of the art which will provide a reference base for the rapid advances in research undertaken from a variety of theoretical standpoints, while in the m.